Chondrogenesis of human adipose derived stem cells for future microtia repair using co-culture technique. (3rd April 2017) - Goh, Bee See; Che Omar, Siti Nurhadis; Ubaidah, Muhammad Azhan; Saim, Lokman; Sulaiman, Shamsul; Chua, Kien Hui
Abstract: Conclusion: In conclusion, these result showed HADSCs could differentiate into chondrocytes-like cells, dependent on signaling induced by TGF- β 3 and chondrocytes. This is a promising result and showed that HADSCs is a potential source for future microtia repair. The technique of co-culture is a positive way forward to assist the microtia tissue. Objective: Reconstructive surgery for the repair of microtia still remains the greatest challenge among the surgeons. Its repair is associated with donor-site morbidity and the degree of infection is inevitable when using alloplastic prosthesis with uncertain long-term durability. Thus, human adipose derived stem cells (HADSCs) can be an alternative cell source for cartilage regeneration. This study aims to evaluate the chondrogenic potential of HADSCs cultured with transforming growth factor-beta (TGF- β ) and interaction of auricular chondrocytes with HADSCs for new cartilage generation. Methods: Multi-lineages differentiation features of HADSCs were monitored by Alcian Blue, Alizarin Red, and Oil Red O staining for chondrogenic, adipogenic, and osteogenic differentiation capacity, respectively. Further, HADSCs alone were culture in medium added with TGF- β 3; and human auricular chondrocytes were interacted indirectly in the culture with and without TGF- β s for up to 21 days, respectively. Cell morphology and chondrogenesis were monitored by inverted microscope. For cell viability, Alamar Blue assay was used to measure the cell viability and the changes in gene expression of auricular chondrocyte markers were determined by real-time polymerase chain reaction analysis. For the induction of chondrogenic differentiation, HADSCs showed a feature of aggregation and formed a dense matrix of proteoglycans. Staining results from Alizirin Red and Oil Red O indicated the HADSCs also successfully differentiated into adipogenic and osteogenic lineages after 21 days. Results: According to a previous study, HADSCs were strongly positive for the mesenchymal markers CD90, CD73, CD44, CD9, and histocompatibility antigen. The results showed HADSCs test groups (cultured with TGF- β 3) displayed chondrocytes-like cells morphology with typical lacunae structure compared to the control group without TGF- β 3 after 2 weeks. Additionally, the HADSCs test groups increased in cell viability; an increase in expression of chondrocytes-specific genes (collagen type II, aggrecan core protein, SOX 9 and elastin) compared to the control. This study found that human auricular chondrocytes cells and growth factor had a positive influence in inducing HADSCs chondrogenic effects, in terms of chondrogenic differentiate of feature, increase of cell viability, and up-regulated expression of chondrogenic genes.